Assessing the Impact of ESG on Financial Performance: Evidence from IDX-Listed Companies (2015–2024) - Natasari, Nada Ardila Eka Ayu (Generate Digital Publishing, 2026)
Objective: This study aims to examine the impact of Environmental, Social, and Governance (ESG) factors on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) during the 2015–2024 period, with financial performance proxied by Return on Assets (ROA). Research Design & Methods: This study employs a quantitative approach using panel data regression analysis with the Fixed Effects Model (FEM). The sample consists of 132 companies with a total of 1,055 observations (unbalanced panel), selected through purposive sampling. ESG variables are measured through environmental performance, social activities, and governance, proxied by board diversity. Findings: The results indicate that the Environmental and Social variables have a positive and significant impact on financial performance, suggesting that better environmental practices and social engagement contribute to higher profitability. Conversely, the Governance variable, proxied by board diversity, exhibits a negative impact on ROA. Simultaneously, ESG variables significantly influence financial performance, although the model’s explanatory power remains relatively limited. Contributions: This study contributes to the growing ESG literature, particularly in the context of emerging markets, by providing empirical evidence on how sustainability practices influence corporate financial performance. Novelty: The novelty of this research lies in the extended observation period (2015–2024), the use of board diversity as a proxy for governance, and the focus on companies listed in Indonesia using an unbalanced panel dataset.